TCO target material powder, preparation method thereof and TCO target material
By spraying stearic acid on the surface of the TCO target powder to form a cladding layer, the problems of easy demolding and high tap density of the TCO target powder are solved, and better demolding performance and sintering effect are achieved.
Patent Information
- Application Number
- CN202411843458.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to achieve easy release of TCO target powder and high tap density, resulting in adhesion problems and degradation of sintering performance during molding.
By spraying the stearic acid-ethanol solution with a mass fraction of 0.5 to 4% at the TCO target powder granulation discharge port, a stearic acid coating layer is formed to improve the powder surface state and reduce the adhesion force.
The tap density and mold release performance of the powder are improved, the damage rate of the sticky mold is reduced, and the sintering performance of the TCO target is improved.
Smart Images

Figure CN119638373A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of target materials, and in particular to a TCO target material powder and a preparation method thereof, and a TCO target material. Background Art
[0002] Powder metallurgy is the main method for producing oxide targets, which has the characteristics of low cost, relatively cheap equipment, and easy control of process parameters. This method involves mixing and powdering, pressing, sintering, and processing. Spray granulation is a commonly used powdering method in powder metallurgy. The granulated powder after spraying is pressed and formed into a target blank. However, during the forming process, the inner wall of the mold and the blank are pressed and adhered, making it difficult to demold the blank. To solve this problem, a release agent needs to be added to the inner wall of the mold or the powder.
[0003] There are two types of release agents: internal release agents and external release agents. External release agents require applying and cleaning the mold surface, which is cumbersome and affects molding efficiency. Generally, internal release agents are added to the slurry, which is then dried to obtain powder. A large amount of release agent exists inside the powder, resulting in low demoulding efficiency. Therefore, a high proportion of release agent needs to be added. The addition of a large amount of organic matter may affect the sintering performance of the powder.
[0004] Chinese patent application CN110143817B discloses a special material for powder injection molding of bismuth stearate-coated lead lanthanum zirconate titanate and a preparation method. The bismuth stearate-coated lead lanthanum zirconate titanate powder is prepared by PLZT powder, polyethylene glycol, polyvinyl butyral, polyoxymethylene, a powder modifier and a lubricating agent, wherein the powder modifier is bismuth stearate.
[0005] In this scheme, bismuth stearate is used to coat the surface of lead lanthanum zirconate titanate powder, breaking the agglomeration between the lead lanthanum zirconate titanate powders and reducing the viscosity of the feed. In addition, in the early stage of sintering, bismuth stearate generates nano-bismuth oxide on the surface of the PLZT powder, which is easily integrated into the lattice, thereby improving the doping efficiency of the bismuth oxide powder and further improving the piezoelectric properties of PLZT.
[0006] The above scheme does not mention that using stearic acid to coat the surface of the granulated powder can reduce the adhesion of the powder, and that the tap density of the powder can be increased by grading and screening the surface-coated powder. While increasing the tap density of the powder, the target material made of the powder is also easier to demold.
[0007] The problem that this solution needs to solve is: how to propose a TCO target powder that is easy to demold and has a high tap density. Summary of the invention
[0008] The purpose of the present invention is to provide a TCO target powder and a preparation method thereof, by spraying stearic acid during the granulation and discharging process of the TCO target powder so that stearic acid is coated on the surface of the TCO target powder, thereby improving the tap density of the powder and the demolding effect of the target prepared by the powder.
[0009] To achieve the above purpose, the present application discloses a method for preparing TCO target powder, wherein the TCO target powder is obtained by preparing slurry, spray granulation, sieving and homogenizing a main material powder and an auxiliary material powder;
[0010] The powder surface obtained by spray granulation contains a spray-coated release agent;
[0011] The release agent is a stearic acid-ethanol solution with a mass fraction of 0.5 to 4% of stearic acid;
[0012] The main material powder is In2O3 powder or SnO2 powder;
[0013] The auxiliary material powder is selected from at least one of ZnO powder, SbO powder, SnO2 powder, Ta2O5 powder and CdO powder, and is a different type of powder from the main material powder;
[0014] By spraying a stearic acid-ethanol solution with a mass fraction of 0.5 to 4% of stearic acid on the surface of the powder obtained at the granulation discharge port, and as the ethanol solution evaporates during the drying process of the powder, a stearic acid coating layer is formed, which can improve the surface state of the powder, reduce the surface roughness of the powder, improve the powder fluidity, improve the tap density of the powder and the demoulding performance of the pressing molding, and reduce the sticking mold breakage rate.
[0015] Preferably, the specific operation of preparing the slurry is: mixing the main material powder, the auxiliary material powder and pure water, grinding once to obtain a solution, then adding a binder, grinding again to obtain a slurry;
[0016] The solid content of the solution is 40-70%, and the mass ratio of the main material powder to the auxiliary material powder is 90-99:1-10;
[0017] The purity of the main material powder and the auxiliary material powder is 4N, and the D50 particle size is less than 1μm.
[0018] Preferably, the binder is selected from at least one of polyvinyl alcohol, polyethylene oxide and cyclodextrin, and the mass of the binder is 1 to 5% of the total mass of the main material powder and the auxiliary material powder.
[0019] Preferably, the rotation speed of the first grinding and the second grinding is 500-1200 rpm, and the time is 8-10 hours.
[0020] Preferably, during the spray granulation process, the atomizing disk speed is 8000-12000 rpm, and the feed pump speed is 30-60%;
[0021] The inlet temperature of spray granulation is 180-240°C, and the outlet temperature is 80-105°C;
[0022] The spraying rate of the stearic acid-ethanol solution is 2-10% of the spray granulation discharge rate.
[0023] Preferably, the specific operation of sieving is: passing the powder obtained by granulation through 40 mesh, 80 mesh, 150 mesh, 200 mesh, 250 mesh, and 400 mesh sieves respectively to obtain powders with particle sizes of 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh.
[0024] Preferably, the mass percentages of powders of 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh during homogenization are 5-10:20-40:20-40:20-30:1-5, and the sum of the mass percentages of powders of 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh during homogenization is 100;
[0025] The homogenizing speed is 10-15 rpm, and the homogenizing time is 2-4 hours.
[0026] In addition, a TCO target powder is provided, which is prepared by the above-mentioned method for preparing the TCO target powder.
[0027] In addition, a TCO target material is provided, which is prepared from the above-mentioned TCO target material powder.
[0028] The beneficial effects of the present invention are:
[0029] The invention provides a TCO target material powder and a preparation method thereof. A stearic acid-ethanol solution with a mass fraction of 0.5 to 4% of stearic acid is sprayed on the surface of the powder obtained at a granulation discharge port, and as the ethanol solution evaporates during the drying process of the powder, a stearic acid coating layer is formed. The surface state of the powder can be improved, the surface roughness of the powder can be reduced, and the powder fluidity can be improved, thereby improving the tap density of the powder and the demoulding performance of the pressing molding, and reducing the sticking mold breakage rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a spray granulation homogenization system, in which 1 is the spray tower body, 2 is the discharge port, 3 is the stearic acid ethanol solution sprayer, 4 is the grading vibration screen, 5 is the receiving tank, 6 is the PLC control system, 7 is the vacuum feeder, 8 is the homogenizer, 9 is the vibration screen, 10 is the control line, and 11 is the powder pipeline. DETAILED DESCRIPTION
[0031] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0032] Example 1
[0033] In2O3 powder and ZnO powder with a purity of 4N and a D50 particle size of less than 1 μm were added to pure water at a mass ratio of 95:5, and ground for 9 hours at a speed of 800 rpm to obtain a mixed solution with a solid content of 55%, and then polyvinyl alcohol of 3% of the total mass of the In2O3 powder and ZnO powder was added and ground for 9 hours at a speed of 800 rpm to obtain a slurry;
[0034] The slurry is spray granulated and homogenized. The structural diagram of the spray granulation and homogenization system can be seen Figure 1 ; It includes a spray tower body 1, a graded vibrating screen 4, a material receiving tank 5, a vacuum feeder 7, a homogenizer 8, and a vibrating screen 9 connected in sequence; the lower part of the spray tower body 1 is a feed port 2, and a stearic acid ethanol solution sprayer 3 is provided at the entrance of the feed port 2; the material receiving tank 5, the vacuum feeder 7, the vacuum feeder 7, and the homogenizer 8 are all connected through a powder pipeline 11; a PLC control system 6 for controlling each device is also provided, which is connected to each device through a control line 10; the subsequent embodiments and comparative examples are all implemented using this system, and the subsequent cases will not be described repeatedly;
[0035] The atomizing disk speed during the spray granulation process is 10000rpm, the feed pump speed is 45%, the inlet temperature of the spray granulation is 210°C, the granulation outlet temperature is 90°C, and a stearic acid-ethanol solution with a mass fraction of 2.5% of stearic acid is sprayed at the granulation outlet through a stearic acid ethanol solution sprayer 3, the spray granulation discharge rate is 10kg / h, and the stearic acid-ethanol solution spray rate is 0.5kg / h, to obtain a powder coated with stearic acid on the surface, and then the powder coated with stearic acid on the surface is passed through 40 mesh, 80 mesh, 150 mesh, 200 mesh, 250 mesh, and 400 mesh sieves to obtain 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh powders coated with stearic acid on the surface;
[0036] Then, the surface-coated stearic acid powders of 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh were mixed in a mass percentage of 7:35:30:25:3 and homogenized at a speed of 13 rpm for 3 hours to obtain TCO target powder.
[0037] Example 2
[0038] In2O3 powder and ZnO powder with a purity of 4N and a D50 particle size of less than 1 μm were added to pure water at a mass ratio of 90:10, and ground for 10 hours at a speed of 500 rpm to obtain a mixed solution with a solid content of 40%, and then polyvinyl alcohol of 1% of the total mass of In2O3 powder and ZnO powder was added and ground for a second time at a speed of 500 rpm for 10 hours to obtain a slurry;
[0039] The slurry is subjected to spray granulation, wherein during the spray granulation process, the rotation speed of the atomizing disk is 8000 rpm, the feed pump speed is 30%, the inlet temperature of the spray granulation is 180° C., the granulation outlet temperature is 80° C., and a stearic acid-ethanol solution with a mass fraction of 2.5% of stearic acid is sprayed at the granulation outlet, the spray granulation discharge rate is 10 kg / h, and the spray rate of the stearic acid-ethanol solution is 0.5 kg / h, to obtain a powder coated with stearic acid on the surface, and then the powder coated with stearic acid on the surface is passed through 40 mesh, 80 mesh, 150 mesh, 200 mesh, 250 mesh, and 400 mesh sieves to obtain 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh powder coated with stearic acid on the surface;
[0040] Then, the surface-coated stearic acid powders of 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh were mixed in a mass percentage of 5:40:24:30:1 and homogenized at a speed of 10 rpm for 4 hours to obtain TCO target powder.
[0041] Example 3
[0042] In2O3 powder and ZnO powder with a purity of 4N and a D50 particle size of less than 1 μm were added to pure water at a mass ratio of 99:1, and ground for 8 hours at a speed of 1200 rpm to obtain a mixed solution with a solid content of 70%, and then polyvinyl alcohol of 5% of the total mass of the In2O3 powder and the ZnO powder was added and ground for 8 hours at a speed of 1200 rpm to obtain a slurry;
[0043] The slurry is subjected to spray granulation, wherein during the spray granulation process, the rotation speed of the atomizing disk is 12000 rpm, the feeding pump speed is 60%, the inlet temperature of the spray granulation is 240° C., the granulation outlet temperature is 105° C., and a stearic acid-ethanol solution with a mass fraction of 2.5% of stearic acid is sprayed at the granulation outlet, the spray granulation discharge rate is 10 kg / h, and the spray rate of the stearic acid-ethanol solution is 0.5 kg / h, to obtain a powder coated with stearic acid on the surface, and then the powder coated with stearic acid on the surface is passed through 40 mesh, 80 mesh, 150 mesh, 200 mesh, 250 mesh, and 400 mesh sieves to obtain 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh powder coated with stearic acid on the surface;
[0044] Then, the surface-coated stearic acid powders of 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh were mixed in a mass percentage of 10:25:40:20:5 and homogenized at a speed of 15 rpm for 2 hours to obtain TCO target powder.
[0045] Example 4
[0046] The method is substantially the same as Example 1, except that a stearic acid-ethanol solution having a mass fraction of 0.5% stearic acid is used as a mold release agent.
[0047] Example 5
[0048] The method is substantially the same as Example 1, except that a stearic acid-ethanol solution having a mass fraction of 4% stearic acid is used as a mold release agent.
[0049] Example 6
[0050] In2O3 powder and ZnO powder with a purity of 4N and a D50 particle size of less than 1 μm were added to pure water at a mass ratio of 95:5, and ground for 9 hours at a speed of 800 rpm to obtain a mixed solution with a solid content of 55%, and then polyvinyl alcohol of 3% of the total mass of In2O3 powder and ZnO powder was added and ground for 9 hours at a speed of 800 rpm to obtain a slurry;
[0051] The slurry was spray granulated, during which the atomizing disk speed was 10000 rpm, the feed pump speed was 45%, the inlet temperature of the spray granulation was 210°C, the granulation outlet temperature was 90°C, and a stearic acid-ethanol solution with a mass fraction of 2.5% of stearic acid was sprayed at the granulation outlet. The spray granulation discharge rate was 10 kg / h, and the spray rate of the stearic acid-ethanol solution was 0.5 kg / h to obtain a powder coated with stearic acid on the surface. The powder coated with stearic acid on the surface was then passed through a 40-mesh sieve and homogenized at a speed of 13 rpm for 3 hours to obtain a TCO target powder.
[0052] Comparative Example 1
[0053] It is basically the same as Example 1, except that the same mass of stearic acid is not coated on the surface of the target powder in the form of spray coating, but is ground together with In2O3 powder and ZnO powder in the form of doping and doped into the interior of the target powder.
[0054] Comparative Example 2
[0055] The method is substantially the same as Example 1, except that a stearic acid-ethanol solution having a mass fraction of 0.3% stearic acid is used as a mold release agent.
[0056] Comparative Example 3
[0057] The method is substantially the same as Example 1, except that a stearic acid-ethanol solution having a mass fraction of 5% stearic acid is used as a mold release agent.
[0058] Comparative Example 4
[0059] The method is substantially the same as Example 1, except that a zinc stearate-ethanol solution having a mass fraction of 2.5% of zinc stearate is used as a release agent, wherein the temperature of the zinc stearate-ethanol solution is 70°C.
[0060] Performance Test:
[0061] Powder tap density: Take 100g of sample and add it into the measuring cylinder of the tap density tester. Turn on the vibration until the volume of the powder no longer decreases. Divide the mass of the powder by the volume to get the tap density.
[0062] Number of damaged mucosa: The rotating target cylinder mold is placed on a vibration platform, and the TCO powder is filled into the mold cavity while the mold is vibrating. After the mold is sealed, it is pressed using a cold isostatic press. After the pressing is completed, the pressed cylinder is separated from the mold, and the number of damaged mucosa on the cylinder is counted in the production of 100 target materials.
[0063] The performance test results are shown in Table 1:
[0064] Table 1
[0065]
[0066]
[0067] Conclusion analysis:
[0068] 1. It can be seen from Examples 1-3 that when changing the process parameters of the TCO target powder production process, such as the solid phase content in the grinding process, the amount of binder added, the mass percentage of powders of different particle sizes when making the target powder, etc., the tap density of the target powder will be affected, and the demolding performance of the film will also be affected. Therefore, it can be seen that the process parameters in Example 1 are the optimal parameters.
[0069] 2. It can be seen from Example 1 and Examples 4-5 that when the amount of release agent stearic acid added is reduced or increased, the performance of the target powder will also be affected. In particular, when the amount of release agent added is reduced, the flow between the target powders will be further reduced, thereby affecting the powder tap density. When the amount of release agent added is increased, there is not much change in the tap density and adhesion of the target powder. It can be seen that the amount of release agent stearic acid added in Example 1 is the optimal amount.
[0070] 3. From Example 1 and Example 6, it can be seen that by granulating and drying the target powder, the target powders of different particle sizes are matched by grading and sieving. It can be found that, compared with Example 6, although the number of damaged target membranes is the same, the tap density of the target powder is observed. It can be found that the tap density of Example 1 is increased by 0.12 g / cm 3 , it can be seen that after grading and screening, the combination of powders with different particle sizes is more conducive to improving the tap density of target powder.
[0071] 4. It can be seen from Example 1 and Comparative Example 1 that, under the same mass, stearic acid is coated on the powder surface in the form of spraying or doped into the powder to reduce the adhesion of the target powder. When doped into the powder, the tap density of the target powder is only 1.74 g / cm 3 , the number of damaged mucous membranes reached 35; when coated on the powder surface in the form of spraying, it can effectively improve the fluidity of the powder and reduce the adhesion of the powder. Therefore, the tap density of the target powder obtained reached 2.20g / cm 3 , the number of mucosal damage was only 3, which shows that stearic acid coating powder in the form of spraying achieved good results;
[0072] It should be noted that the coating process of the TCO target powder prepared in the present invention must be carried out by spraying and coating with a release agent during the spray granulation process. If the TCO target powder is placed in a release agent solution for coating after spray granulation, the TCO target powder and water will be dispersed and cannot be coated.
[0073] 5. It can be seen from Example 1 and Comparative Examples 2-3 that when the amount of stearic acid added is further reduced, the target powder cannot be completely coated or the coating layer is too thin due to the small amount of stearic acid, resulting in poor improvement in the fluidity and adhesion of the target powder, causing more mucosal damage; and when the amount of stearic acid added is further increased, although the number of mucosal damage is still only 3, due to the excessively thick coating, the organic matter content in the powder is too high, resulting in difficulty in discharging the organic matter during the sintering process, requiring the debinding stage to be extended, increasing the sintering cost.
[0074] 6. It can be seen from Example 1 and Comparative Example 4 that when stearate is dissolved in ethanol solution and coated on the surface of the target powder by spraying, the effect is far worse than that of stearic acid coating. It is speculated that this may be because stearic acid is a long-chain fatty acid, and stearate exists in a crystalline or colloidal form. In terms of coating, stearic acid can be better and more evenly coated on the surface, and can be directly adsorbed to the powder through van der Waals forces or hydrogen bonds, while stearate forms crystals with metal ions first, and its adsorption will be worse. Therefore, it is less effective in improving the tap density of the target powder and reducing the adhesion of the target powder.
[0075] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing TCO target powder, characterized in that: The TCO target powder is obtained by preparing slurry, spray granulation, sieving and homogenizing the main material powder and the auxiliary material powder; The powder surface obtained by spray granulation contains a spray-coated release agent; The release agent is a stearic acid-ethanol solution with a mass fraction of stearic acid of 0.5 to 4%; The main material powder is In2O3 powder or SnO2 powder; The auxiliary material powder is selected from at least one of ZnO powder, SbO powder, SnO2 powder, Ta2O5 powder and CdO powder, and is a different type of powder from the main material powder.
2. The method for preparing TCO target powder according to claim 1, characterized in that: The specific operation of preparing the slurry is: mixing the main material powder, the auxiliary material powder and pure water, grinding once to obtain a mixed liquid, then adding a binder, grinding twice to obtain a slurry; The solid content of the solution is 40-70%, and the mass ratio of the main material powder to the auxiliary material powder is 90-99:1-10; The purity of the main material powder and the auxiliary material powder is 4N, and the D50 particle size is less than 1 μm.
3. The method for preparing TCO target powder according to claim 2, characterized in that: The binder is selected from at least one of polyvinyl alcohol, polyethylene oxide and cyclodextrin, and the mass of the binder is 1-5% of the total mass of the main material powder and the auxiliary material powder.
4. The method for preparing TCO target powder according to claim 2, characterized in that: The rotation speed of the first grinding and the second grinding is 500-1200 rpm, and the time is 8-10 hours.
5. The method for preparing TCO target powder according to claim 1, characterized in that: During the spray granulation process, the atomizing disk speed is 8000-12000 rpm, and the feed pump speed is 30-60%; The inlet temperature of spray granulation is 180-240°C, and the outlet temperature is 80-105°C; The spraying rate of the stearic acid-ethanol solution is 2-10% of the spray granulation discharge rate.
6. The method for preparing TCO target powder according to claim 1, characterized in that: The specific operation of the sieving is: passing the powder obtained by granulation through 40 mesh, 80 mesh, 150 mesh, 200 mesh, 250 mesh and 400 mesh sieves respectively to obtain powders with particle sizes of 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh and 250-400 mesh.
7. The method for preparing TCO target powder according to claim 1, characterized in that: During the homogenization process, the mass percentages of the powders of 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh are 5-10:20-40:20-40:20-30:1-5, and the sum of the mass percentages of the powders of 40-80 mesh, 80-150 mesh, 150-200 mesh, 200-250 mesh, and 250-400 mesh is 100; The homogenizing speed is 10-15 rpm, and the homogenizing time is 2-4 hours.
8. A TCO target powder, characterized in that: The target powder is prepared by the method for preparing the TCO target powder according to any one of claims 1 to 7.
9. A TCO target material, characterized in that: Prepared from the TCO target powder according to claim 8.
Citation Information
Patent Citations
A bismuth stearate-coated lead zirconate titanate lanthanum powder injection molding material and its preparation method
CN110143817B